2020
DOI: 10.1088/1361-6668/ab9acf
|View full text |Cite
|
Sign up to set email alerts
|

Fe(Se,Te) from melting routes: the influence of thermal processing on microstructure and superconducting properties

Abstract: Superconducting properties of the Fe(Se,Te) system are directly related to its microstructure. However, in the framework of a not well assessed phase diagram, a large spread of chemico-physical and functional properties is reported for compounds characterized by similar overall chemical compositions. This is in particular observed in materials produced by melting routes, where chemical inhomogeneities and multiple phases are commonly obtained. Both composition and morphology of these inhomogeneities seem to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
4
8
0
Order By: Relevance
“…On the other hand, as can be seen from the phase diagram, the formation of the superconducting phase is highly demanding with respect to the sintering temperature, and its narrow element and temperature intervals also make the synthesis challenging. 7 To prepare high-quality superconducting bulk, various methods have been developed, including mechanical alloying of precursor powder, 8,9 annealing, [10][11][12][13] optimizing sintering procedures, 14,15 varying the secondary sintering temperature or multiple sintering, 16,17 and soaking in different liquids. [18][19][20] Mechanical alloying of precursor powders can generate high melting point metallic phases; however, high viscosity FeSeTe powder easily accumulates during high-energy ball milling, resulting in insufficient grinding and heterophase formation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, as can be seen from the phase diagram, the formation of the superconducting phase is highly demanding with respect to the sintering temperature, and its narrow element and temperature intervals also make the synthesis challenging. 7 To prepare high-quality superconducting bulk, various methods have been developed, including mechanical alloying of precursor powder, 8,9 annealing, [10][11][12][13] optimizing sintering procedures, 14,15 varying the secondary sintering temperature or multiple sintering, 16,17 and soaking in different liquids. [18][19][20] Mechanical alloying of precursor powders can generate high melting point metallic phases; however, high viscosity FeSeTe powder easily accumulates during high-energy ball milling, resulting in insufficient grinding and heterophase formation.…”
Section: Introductionmentioning
confidence: 99%
“…10 On the other side, low-temperature annealing tends to produce dendrites, which cause phase separation and hexagonal phases. 12,13 Immersion of the sample in alcoholic beverages or inorganic acids affects the interstitial iron deintercalation but is not beneficial in strengthening the superconducting phase. Moreover, acid-treated samples typically perform no better than annealed samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to these stable phases, it's always challenging to prepare a completely pure superconducting phase either in single crystal [14,15] or polycrystalline samples [3,7,16,17]. Some of these stable phases, particularly hexagonal δ-Fe x Se and hexagonal Fe 7 Se 8 , typically coexist with the predominant tetragonal β-Fe x Se phase [18] during the growth process and are not suitable for superconducting properties [19][20][21][22][23]. Recent research has demonstrated that convenient synthesis methods at ambient pressure (CSP) are inefficient for improving the critical current properties, grain connectivity, and phase purity of the bulk samples, as well as for practical applications [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%